Heartless hunter - Ciccarelli, Kristen (Ciccarelli, Kristen. Crimson moth, 2024)
In a world where witches face persecution, Rune leads a double life, masquerading as a socialite during the day and transforming into the vigilante known as the Crimson Moth by night, and forms a complicated alliance with the witch hunter Gideon Sharpe, blurring the lines between love and danger.